2020
DOI: 10.17503/agrivita.v42i1.1805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chicken Compost and KCl Fertilizer on Growth, Yield, Post-Harvest Quality of Sweet Corn and Soil Health

Abstract: This study aimed to determine the effects of chicken compost and KCl fertilizer application on the growth, yield, post-harvest quality of sweet corn (Zea mays L. var. saccharata), soil respiration and microbial population. The research was arranged according to a Factorial Random-Block Design consisting of two factors and three replications. The first factor was the dose of chicken compost (0 and 15 t/ha) and the second the dose of KCl fertilizer (0, 50, 100 and 150 kg/ha). The results showed that chicken comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
(46 reference statements)
1
16
1
3
Order By: Relevance
“…Antonius et al(2014) melaporkan, bahwa limbah tandan pisang mengandung bakteri yang mampu menghasilkan asam indol asetat (IAA). Keuntungan lainnya pupuk organik tidak hanya memperbaiki sifat kimia melalui peningkatan pH tanah, tetapi juga biologi tanah (peningkatan populasi mikroba bakteri dan fungi) (Pangaribuan et al 2018). Lebih lanjut Pangaribuan et al (2018) melaporkan bahwa kombinasi pupuk organik dengan Urea dapat mengurangi penggunaan pupuk Urea dan meningkatkan tinggi tanamna, indeks luas daun, kandungan klorofil dan karotenoid daun jagung manis.…”
Section: Pembahasanunclassified
“…Antonius et al(2014) melaporkan, bahwa limbah tandan pisang mengandung bakteri yang mampu menghasilkan asam indol asetat (IAA). Keuntungan lainnya pupuk organik tidak hanya memperbaiki sifat kimia melalui peningkatan pH tanah, tetapi juga biologi tanah (peningkatan populasi mikroba bakteri dan fungi) (Pangaribuan et al 2018). Lebih lanjut Pangaribuan et al (2018) melaporkan bahwa kombinasi pupuk organik dengan Urea dapat mengurangi penggunaan pupuk Urea dan meningkatkan tinggi tanamna, indeks luas daun, kandungan klorofil dan karotenoid daun jagung manis.…”
Section: Pembahasanunclassified
“…The use of dairy-based vermicompost had been reported to increase the growth of greenhouse cucumber [12] and potato [13]. Chicken manure has been widely reported to increase the yield of several vegetables, such as sweet corn [14], komatsuna [15], and kale [16]. Other reports confirmed that poultry manure as an organic fertilizer had a better effect of increasing okra yield [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways of improving soil fertility is by supplementing the soil by organic and inorganic fertilizer that is beneficial to improve the soil fertility and agricultural quality and quantity. 1 Sweet corn is a horticultural crop that has the potential to add to the realization of food security in Nigeria. 2 Sweet corn is much in demand.…”
Section: Introductionmentioning
confidence: 99%